Predictors of severe cerebral ischemia in premature infants - O. V. Remneva; N. I. Fadeeva; Yu. V. Korenovskiy; O. V. Kolyado (Фундаментальная и клиническая медицина, 2019)
Aim. To identify informative predictors of severe cerebral ischemia in preterm neonates.Materials and Methods. Study sample consisted of 80 preterm infants with intrauterine hypoxia or perinatal asphyxia delivered on the 28th-34th week of gestation. Levels of matrix metalloproteinase-9 (MMP-9) and thiobarbituric acid reactive substances (TBARS) as well as activity of antioxidant enzymes superoxide dismutase, catalase, and glutathione peroxidase in cord blood plasma of premature infants were evaluated immediately after birth.Results. As compared to other newborns, neonates with severe cerebral ischemia had higher levels of MMP-9 (MMP-9 > 305.6 ng/mL in 14.6% versus 69.7%, respectively) and TBARS in cord blood plasma.Conclusion. MMP-9 and TBARS measured in cord blood plasma of preterm infants may be utilised in diagnostics of severe cerebral ischemia.